Determination of marketing characteristics of market capacity for electrical automation - Pererva, P. G.; Kobielieva, Tatiana Aleksandrovna; Tkachev, Maksim; Tkacheva, Nadezhda (Сумський державний університет, 2017)
The problems of determining the marketing characteristics of the market products capacity do not have independent technological purposes. As the object of study selected electrical automation. It is proved that the most important characteristic of the market capacity of goods are the demand for them, which consists of several components. To determine the requirements for electrical automation and maintenance of technological equipment under operation, you need to know the industry Park. The technique of determining industry Park, products which do not have independent technological purpose and which are not maintained inventory records, for example, electrical automation of the basic steps of this methodology. The proposals of the authors based on the determination coefficients the applicability of certain types of electrical automation equipment per unit of basic technological equipment of machine-building industries.

Розглянуто питання визначення маркетингових характеристик місткості ринку виробів, що не мають самостійного технологічного призначення. В якості об'єкта дослідження вибрано електротехнічні засоби автоматизації. Доведено, що найважливішою характеристикою ємності ринку виробів є потреба у них, яка складається з декількох складових. Для визначення потреби в електротехнічних засобах автоматизації на ремонт і експлуатацію технологічного обладнання, що знаходяться в експлуатації, необхідно знати його галузевої парк. Розроблена методика визначення галузевого парку виробів, що не мають самостійного технологічного призначення і за якими не ведеться інвентаризаційний облік. На прикладі електротехнічних засобів автоматизації розглянуто основні етапи даної методики. Пропозиції авторів побудовані на визначенні коефіцієнтів застосування окремих типів електротехнічних засобів автоматизації на одиницю основного технологічного обладнання в машинобудівних галузях.
Визначення маркетингових характеристик місткості ринку електротехнічних засобів автоматизації
Keywords: park products; electrical automation products; marketing; coefficients of applicability; processing equipment; парк виробів; електротехнічні засоби автоматизації; маркетинг; коефіцієнти вживаності; технологічне обладнання